Transition Coach Program Implementation Associated with Thirty-Day Readmission Rates in a Community Hospital Setting - Richard A Moore II; Travis Gerke; Derek Bourgoine; Pracha P Eamranond (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Background: With implementation of Medicare policies affecting reimbursement for readmissions, there has been increased emphasis on quality of care during transition from hospital to home. Several models for improved care, such as utilization of transition coaches, have developed to address barriers to quality healthcare that are prevalent in this care transition. Objective: To study the effect of implementation of a transition coach program on thirty-day readmission rates in a community setting serving a predominantly low-income patient population. Design: Retrospective cohort study. 30-day readmission rates of control group were compared to group receiving transition coach services. Setting: 189-bed community hospital. Patients: Medicare or dually-eligible patients admitted between 2/1/12 and 1/31/14. Intervention: Intervention group received transition coach services, including inpatient assessment, at-home assessment and medication reconciliation, and telephone-based follow-up in the thirty days following index hospital admission. Measurements: Data was gathered retrospectively on 30-day readmissions. After adjusting for age, gender, ethnicity, length of stay, and comorbidity, the odds of readmission were then assessed through logistic regression. Results: After adjusting for age, sex, length of stay, and comorbidity, odds ratio for readmission remained higher for those receiving transition coach services, with 30-day odds ratios of 1.55 (95% CI: 1.15-2.08, p = 0.004) during year one and 1.88 (1.40-2.53, p < 0.001) during year two. Conclusions: Though limited by design, it did not appear that use of transition coaches among a high-risk elderly population decreased rates of all-cause readmission in this community setting.